Microbial etiology of hospital-acquired pneumonia/ventilator-associated pneumonia in hospitals of Shandong Province - Zhang, Gui; Cheng, Yanpeng; Hu, Xiaojie; Li, Weiguang; Sun, Jian; Chen, Zhiyuan; Xu, Hua (The Journal of Infection in Developing Countries, 2025)
Introduction: Nosocomial pneumonia includes hospital-acquired pneumonia without association with mechanical ventilation (HAP) and ventilator-associated pneumonia (VAP). The prevalence and microbial etiology of HAP/VAP in Shandong Province were evaluated to provide a reference for hospital infection control. Methodology: Data was obtained from patients with HAP/VAP admitted to hospitals within the network of Shandong Provincial Hospital infection management and monitoring from 2019 to 2023. Results: The prevalence of HAP/VAP showed an overall downward trend across the 5-year period, with range of 0.68–0.43% and 0.067–0.04%, respectively. A total of 83,533 HAP and 7,205 VAP cases were diagnosed (male-to-female ratio of 1.89:1 and 2.13:1; and median age of 67.7 and 64.2 years), among which 47,862 and 9,806 strains were isolated from patients with HAP/VAP, respectively. The primary pathogens in HAP/VAP were similar, and included Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae. The antimicrobial susceptibility was low, with lesser susceptibility in VAP. The major multidrug resistant microorganisms (MDROs) were identical in HAP/VAP; and MDR-A. baumannii had the highest detection rate, followed by MDR-Staphylococcus. aureus and MDR-P. aeruginosa. The Mantel-Haenszel χ2 test suggested that there was a linear relationship between the detection rate of MDR-P. aeruginosa and MDR-S. aureus and time (p < 0.001 for MDR-P. aeruginosa in HAP/VAP and MDR-S. aureus in HAP; p = 0.023 for MDR-S. aureus in VAP). Conclusions: The infection rates of HAP and VAP displayed a declining trend. The major pathogens were similar in HAP and VAP, but with low antimicrobial susceptibility and high detection rate of MDROs.